Lipidome analyses reveal radiation induced remodeling of glycerophospholipid unsaturation in lung tumor - He, Jingquan; Yuan, Qingqing; Gao, Song; Wang, Yue; Lai, Haigen; Wang, Kaiting; Zhou, Xiaoman; Zhang, Zicheng (Frontiers in Immunology, 2024)
Radiotherapy is a pivotal treatment for lung cancer, significantly impacting tumor control and patient quality of life. Despite its benefits, the molecular mechanisms underlying radiotherapy-induced biological alterations in lung cancer cells remain inadequately understood. In this study, we employed a mass spectrometry-based lipidomics approach to investigate lipid profile changes in a lung cancer mouse model post-radiation. Lewis lung carcinoma (LLC) cells were injected into C57BL/6J mice, followed by radiation treatment with varying split doses. Our results showed an increase in sterol lipids and a decrease in glycerolipids, specifically triacylglycerides, indicating disrupted lipid storage. Additionally, we observed significant changes in glycerophospholipid unsaturation, suggesting a remodeling of membrane properties that may influence cell survival. Linear regression analysis demonstrated a significant negative correlation between glycerophospholipid unsaturation index and tumor weight, indicating a potential role in radiation-induced tumor cell death. These findings provide new insights into the lipid metabolic pathways affected by radiotherapy and could inform the development of improved therapeutic strategies for lung cancer treatment.